MicroRNAs in Preeclampsia - Skalis, Georgios; Katsi, Vasiliki; Miliou, Antigoni; Georgiopoulos, Georgios; Papazachou, Ourania; Vamvakou, Georgia; Nihoyannopoulos, Petros; Tousoulis, Dimitrios; Makris, Thomas (MicroRNA, 2019)
Preeclampsia (PE) continues to represent a worldwide problem and challenge for both clinicians and laboratory-based doctors. Despite many efforts, the knowledge acquired regarding its pathogenesis and pathophysiology does not allow us to treat it efficiently. It is not possible to arrest its progressive nature, and the available therapies are limited to symptomatic treatment. Furthermore, both the diagnosis and prognosis are frequently uncertain, whilst the ability to predict its occurrence is very limited. MicroRNAs are small non-coding RNAs discovered two decades ago, and present great interest given their ability to regulate almost every aspect of the cell function. A lot of evidence regarding the role of miRNAs in pre-eclampsia has been accumulated in the last 10 years. Differentially expressed miRNAs are characteristic of both mild and severe PE. In many cases they target signaling pathway-related genes that result in altered processes which are directly involved in PE. Immune system, angiogenesis and trophoblast proliferation and invasion, all fundamental aspects of placentation, are controlled in various degrees by miRNAs which are up- or downregulated. Finally, miRNAs represent a potential therapeutic target and a diagnostic tool.
Keywords: miRNA